Chemical characterization and bioactive compounds of jambolan pulp ice cream (Research, Society and Development, 2022)
Some fruits have vitamins, natural pigments and industrialization potential, such as jambolan (Syzygium cumini). The objective of the present work was to characterize chemically and to evaluate the content of bioactive compounds in ice cream based on jambolan pulp. Formulations of ice cream with different concentrations of jambolan pulp were elaborated: 0% (T1), 5% (T2), 10% (T3), 15% (T4) and 20% (T5). Analyzes of chemical composition, pH, soluble solids, titratable total acidity, overrun, phenolic compounds, antioxidant activity and anthocyanins were performed. The effect of the addition of jambolan pulp on the ice cream formulations promoted a decrease in the soluble solids content (variation of 45.51 to 34.02 Brix), pH (variation of 6.77 to 4.35) and increase of humidity (range of 63.90 to 67.23 g 100 g -1). However, there was a significant increase in the protein content (variation of 12.10% to 14.09), lipids (variation of 14.35% to 15.08), ashes (variation from 0.73% to 1.29%) and dietary fiber (variation of 0.00% to 1.03%) in the treatment with a higher proportion of jambolan pulp. The formulations with a higher proportion of jambolan pulp also presented higher phenolic, anthocyanin and antioxidant activity (p≥0.05) compared to control (T1). The results indicated that the addition of at least 15% of jambolan pulp in the ice cream formulations is already sufficient for the product to have bioactive properties. It can be concluded that the addition of jambolan pulp to the ice cream showed significant increases in nutritional values and bioactive properties. Therefore, jambolan is a potential ingredient in the edible ice cream industry.